PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP PEMAHAMAN DAN KEMANDIRIAN SISWA MATA PELAJARAN PPKN DI SDN BANYUAJUH 2 KAMAL - Faisal, Bagus Imam; Arifin, Zainal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
Teachers play an important role in improving the quality of student education through the design Because with the learning model used in the learning process, students tend to be active and learn well. The aim of this research is to determine the effect of the problem-based learning (PBL) model on students' understanding and independence in Citizenship Education subjects at Sdn Banyuajuh 2 Kamal. The research design used in this research is a one-group post-test design. In this design, the sample is given a pre-test (initial test) before giving treatment and a post-test (final test) at the end of the study. Test questions and quizzes function as tools to determine understanding and independence. Data collection techniques are the most important research stage because the main aim of research is to collect data. The Sig value obtained. 0.05 < 0.05, then H1 is accepted, which means that the PBL model variables influence the understanding variables of class 5 students at SDN Banyuajuh 2 Kamal and a Sig value is obtained. 0.01 < 0.05 then H1 is accepted which means the variables in the PBL model have an influence on the independent variables of grade 5 students at SDN Banyuajuh 2 Kamal.